Mycobacterium tuberculosis H37Rv infection regulates alternative splicing in Macrophages. Issue 1 (1st January 2018) - Zhang, Wei; Niu, Chen; Fu, Rui-Yang; Peng, Zheng-Yu
ABSTRACT: Objective: The objective of this study was to evaluate the expression of genes encoding SR proteinsand alternative splicing of IL4 and TLR4 in Mycobacterium tuberculosis (M. tb) H37Rv-infected macrophages. Materials and methods: THP-1 cells were induced to differentiate into macrophages with 200 nM PMA, and H37Rv strains were used for macrophage infection. After RNA extraction, qRT-PCR was performed to evaluate the expression of many SR proteins as well as the alternative splicing of IL4 and TLR4. Results: IL4 and TLR4 play significant roles in host immunity to tuberculosis. The level of IL-4 splice variants in THP-1 cells increased after M. tb H37Rv infection. Three splice variants of TLR4 were detected in M. tb -infected THP-1 cells, when compared with uninfected controls; the expression level of these splicing variants in M. tb -infected THP-1 cell was down-regulated. Since SR proteins are RNA-binding proteins that regulate RNA splicing, the expression of SR proteins was examined, and SRSF2 and SRSF3 were significantly down-regulated. In addition, splicing factors SRp75 and SF3a were also significantly down-regulated post M. tb infection. Conclusion: Our findings indicate that alternative splicing may be involved in host gene regulation post M. tb infection of macrophage cells.